Corroboration under the Evidence Act 1950 and Islamic law: a comparative appraisal - Shair Mohamad, Mohd Akram; , (Serials Publications, 2010)
As a general rule under the Malaysian Evidence Act 1950, which encapsulates the English common law, and unlike the situation in some civil law countries and Islamic law, evidences does not need to be supported to found a conviction on to prove a civil claim. However, at common law and under the Evidence Act 1950, a small number of situations heve developed in which actual corroboration is necessary, especially in criminal matters, while in others there is a mandatory requirement that a trial judge must warn himdelf of the dangersof convicting in its absence. Further, there is a controversy as to whether a previous statement under section 157 constitutes true corroboration. In Malaysia, the highest court has ruled it is, following similar sentiments in India and Brunei which hae similar legislations, while Singapore has taken a different approach by saying that the previous statement of a witness cannot constitute corroboration, as its value is only to show the witness consistency with his conduct of making the complaint. The article adresses partinent issues pertaining to corroboration from the common law, the Evidence Act and Islamic law viewpoints.